2016
DOI: 10.3855/jidc.7215
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mutational changes in the embB among the ethambutol-resistant strains of Mycobacterium tuberculosis in Iran

Abstract: Introduction: Early detection of drug resistant tuberculosis is one of the main priorities of TB control program. Ethambutol (EMB) is a firstline anti-TB drug that is effective for preventing treatment failures caused by Mycobacterium tuberculosis strains that are resistant to other drugs. The aim of this study was to sequence the embB gene to characterize the mutations causing resistance to EMB and to analyze the relationship between bacterial genotype and EMB resistance among M. tuberculosis isolates in Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The discordance between phenotypic AST of Emb and mutations in the embCAB operon has also been reported by investigators from other countries and Iran 3133. In the study from Iran, embB mutations were investigated in a few Iranian cities, and based on their results from four Emb-resistant isolates recovered from Tehran, only one 306 mutation was detected, and in some cities no 306 mutation was demonstrated among the phenotypic Emb-resistant isolates 33. In the current study, we investigated the most common mutation sites within the three genes embA, embB , and embC .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The discordance between phenotypic AST of Emb and mutations in the embCAB operon has also been reported by investigators from other countries and Iran 3133. In the study from Iran, embB mutations were investigated in a few Iranian cities, and based on their results from four Emb-resistant isolates recovered from Tehran, only one 306 mutation was detected, and in some cities no 306 mutation was demonstrated among the phenotypic Emb-resistant isolates 33. In the current study, we investigated the most common mutation sites within the three genes embA, embB , and embC .…”
Section: Discussionsupporting
confidence: 61%
“…Among the Emb phenotypic resistant isolates, only two were detected by mutations within the embCAB operon. The discordance between phenotypic AST of Emb and mutations in the embCAB operon has also been reported by investigators from other countries and Iran 3133. In the study from Iran, embB mutations were investigated in a few Iranian cities, and based on their results from four Emb-resistant isolates recovered from Tehran, only one 306 mutation was detected, and in some cities no 306 mutation was demonstrated among the phenotypic Emb-resistant isolates 33.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, other studies also found discord between phenotypic resistance assays and genotypic changes in the embCAB operon [50]. EmbB mutations were also detected in 5% of phenotypically EMB s isolates which varied from 14.3 [54] to 45% [8] in previous studies. Earlier studies did not report the A346P substitution in EMB s isolates.…”
Section: Discussionmentioning
confidence: 82%